Applying Cooperative Learning to Data Handling Lessons in Elementary School - Mulyono, Mulyono (SEARCH: Science Education Research Journal, 2026)
Mathematics learning in data management materials in elementary schools still faces obstacles due to low activity and student understanding due to the dominance of lecture methods. This condition demands the implementation of a more participatory and collaborative learning model. This study aims to describe the application of the Cooperative Learning model in data management learning in students in grades V-C SD Negeri 19 Sorong City and examine its impact on learning activities and student understanding. This study uses a qualitative descriptive approach with quantitative support and descriptive class observation design. The subject of the study is a student of class V-C SD Negeri 19 Sorong City. Data collection techniques include observation of the learning process, group discussions, questions and answers, and assignments, while data analysis is carried out through subtraction, presentation, and conclusion drawn. The results of the study show that the application of the Cooperative Learning model is able to increase student activities in group discussions, encourage cooperation between students, and improve understanding of data management concepts. Students are more actively involved in observing, processing, and presenting data in a simple way. In conclusion, the Cooperative Learning model is effectively applied to data management learning in elementary schools and has positive implications for more interactive, collaborative, and student-centered learning practices.